Taphonomy, distribution and palaeoecology of stalked barnacles (Crustacea, Cirripedia) from the Bohemian Cretaceous Basin, Czech Republic - Kočová Veselská, Martina; Kočí, Tomáš (Geology, Geophysics and Environment, 2015)
-